PROSES EVALUASI PROGRAM SIARAN RHYTHM & BREEZE PADA 106.6 FM V RADIO JAKARTA - Wiratri Anindhita (Jurnal Komunikasi dan Bisnis, 2013)
Radio as a one of mass communication media has an important role. For example, providing information, educating, and entertaining their listeners. As one of the radio station in Jakarta, 106.6 FM V Radio Jakarta has programs that designed to give what their listeners need. One of them is Rhythm & Breeze. In the process, the Rhythm & Breeze program need to be evaluated to maintain and to increase its quality. The evaluation process performed include the evaluation of the program content, the announcer and the financial sector. This researchÂ  found that the evaluation process on the program content is performed when the team find a problem with the content of the program. The content evaluation process continued into the formal forum with the board of director, to find a decision that would be carried out by the team of the program. On the evaluation process of program announcer, the evaluation starts from board of director that monitor the program announcer. After that, the board of director will hold a formal meeting with the station manager and the program teams to find a decision. On the evaluation process of the financial sector, the financial department will evaluate the financial condition of the company every single month. If they found negative results, they would hold formal meeting with the board of director and the program team, to find the solutions. The evaluation process of the Rhythm & Breeze program content, the team have the authority to determine a decision. On the evaluation process of the program announcer, the board of director has the authority to determine a decision. While on the evaluation process of the financial sector, the financial department has been given more authority from the board of director in determining the evaluation process of financial sector, and in taking a decision for the 106.6 FM V Radio Jakarta financial problems. Keywords: Evaluation, Process of Broadcasting Program, Radio